Buccal ureteroplasty options, techniques, long-term results - A. A. Volkov; N. V. Budnik; O. N. Zuban; I. D. Mustapaev; M. A. Abdulaev; A. V. Muziev (Исследования и практика в медицине)
Purpose of the study. Surgical treatment of extended strictures and obliterations of the ureter is still a complicated problem of modern urology. The aim of the study was to analyze our own experience of ureteral replacement plastic surgery with buccal graft, i.e buccal ureteroplasty (BU) with its extended strictures/obliterations.Patients and methods. We’ve observed 25 patients who underwent BU. The lower third of the ureter was affected in 3 (12.0 %) cases, the lower third and the mouth of the ureter was affected in 7 people (28.0 %), the middle third in 2 (8.0 %), the upper third in 5 patients (20.0 %), the combined lesion of the upper third of the ureter and the pelvic‑ureteral segment (PUS) was in 8 (32.0 %) patients. All patients underwent repeated operations on a ureter, all revealed a significant comorbid background. The surgery was performed with a tubularized buccal graft in 13 (52.0 %), the onlay technique was applied in 12 (48.0 %). Laparoscopic surgery was performed in 10 (40.0 %) patients, surgical aid was carried out in an open way in 15 (60 %).Results. Severe complications according to the Clavien‑Dindo classification, requiring hospitalization of patients in the intensive care unit with organ dysfunction, as well as lethal outcomes were absent. The follow‑up period of patients ranged from 1 to 57 months (an average of 14.7 months). One patient after laparoscopic BU with a tubular graft had a short (1 mm) stenosis in the anastomosis area for 6 months of follow‑up, which was successfully eliminated by laser endoureterotomy. During the entire follow‑up period, residual hydronephrosis was recorded in 4 patients (16.0 %) against the background of complete patency of the anastomosis. A control flexible ureteroscopy performed in 16 (64.0 %) patients did not reveal rejection of the buccal graft. There are still 20 patients under our supervision.Conclusion. Our experience shows that the implementation of BU is possible on any part of the VMP using various techniques. This operation can be regarded as the "second" line of surgical treatment of strictures and obliterations of the ureter, especially after unsuccessful attempts of other reconstructions in a group of patients with severe concomitant pathology.